TANTANGAN DALAM PENERAPAN KURIKULUM MERDEKA PADA TINGKAT SEKOLAH DASAR: (STUDI TEMUAN DARI PERSPEKTIF BERAGAM) - Nisaul Khaira (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Technological developments and urgent needs encourage curriculum changes. The Merdeka Curriculum is expected to facilitate students' self-development. A qualitative study with an exploratory case study desig5n examines the challenges and strategies for implementing the Merdeka Curriculum at the elementary school level in Mutiara District, Pidie Regency. Researchers interviewed and observed education officials, school principals, teachers and students to gain a comprehensive understanding. The study results show a positive response to the Merdeka Curriculum from all stakeholders. Respondents were enthusiastic about learning and applying the values of the Merdeka Curriculum in learning. However, implementation faces challenges, including teacher readiness, school support in providing material and non- material facilities, and the diversity of students in the class. Nevertheless, joint efforts continue to be made to maximize the advantages of the Merdeka Curriculum and overcome shortcomings. The Merdeka Curriculum is a benchmark for learning progress in schools and encourages continuous evaluation to develop student potential.